KARATERISTIK MORFOLOGI DAUN TANAMAN TOMAT (SOLANUM LYCOPERSICUM L.) PADA KONDISI LINGKUNGAN YANG BERBEDA - Herina, Nandia; Vauzia; Violita; Chatri, Moralita (Jurnal Biogenerasi, 2025)
Tomato (Solanum Lycopersicum L.) is a horticultural plant from the Solanaceae family that has potential as a vegetable. Tomatoes can grow in various land conditions, both in highlands and lowlands. However, the production of this plant has not been optimal in meeting the needs of the community recently due to various environmental factors. To adapt to different environmental stress conditions, it is important to understand how the plant responds, particularly the morphological responses of tomato leaves in various environmental conditions.This research was conducted from September 2024 to January 2025 in Kamang Magek and the city of Padang. The research method is experimental, comparing the morphological characteristics of tomato leaves, including leaf length and width, petiole length, and the number of leaf veins. The data were analyzed using a t-test at a 5% significance level.The results show that the morphological characteristics of tomato leaves exhibit significant differences in terms of leaf length and width between Kamang Magek and the city of Padang. The average leaf length in Kamang Magek is about 55.5 cm, while in the city of Padang, it is 25.60 cm. The average leaf width in Kamang Magek is approximately 23.30 cm, whereas in the city of Padang, it is 22.95 cm. However, when considering petiole length and the number of leaf veins, no significant differences were observed between the city of Padang and Kamang Magek.